A Tale of Two Cities: Software Developers Working from Home During the COVID-19 Pandemic. - Ford Robinson, Denae; Storey, Margaret-Anne; Zimmermann, Tom; Bird, Christian; Jaffe, Sonia; Maddila, Chandra; Butler, Jenna; Houck, Brian; Nagappan, Nachi (ArXiv, 2020)
The COVID-19 pandemic has shaken the world to its core and has provoked an overnight exodus of developers that normally worked in an office setting to working from home. The magnitude of this shift and the factors that have accompanied this new unplanned work setting go beyond what the software engineering community has previously understood to be remote work. To find out how developers and their productivity were affected, we distributed two surveys (with 3,634 responses)—weeks apart to understand the presence and prevalence of the benefits, challenges, and opportunities to improve this special circumstance of remote work. From our thematic qualitative analysis and statistical quantitative analysis, we find that there is a dichotomy of developer experiences influenced by many different factors (that for some are a benefit, while for others a challenge). For example, a benefit for some was being close to family members but for others having family members share their working space and interrupting their focus, was a challenge. Our surveys led to powerful narratives from respondents and revealed the scale at which these experiences exist to provide insights as to how the future of (pandemic) remote work can evolve.